2003
DOI: 10.1037/0021-9010.88.6.989
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion and Performance in Groups: A Meta-Analytic Clarification of Construct Relations.

Abstract: Previous meta-analytic examinations of group cohesion and performance have focused primarily on contextual factors. This study examined issues relevant to applied researchers by providing a more detailed analysis of the criterion domain. In addition, the authors reinvestigated the role of components of cohesion using more modern meta-analytic methods and in light of different types of performance criteria. The results of the authors' meta-analyses revealed stronger correlations between cohesion and performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
870
5
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 989 publications
(931 citation statements)
references
References 117 publications
32
870
5
24
Order By: Relevance
“…Group cohesion has been described as a bonding force consisting of four factors, namely attraction to the group as a whole and to individual members of the group, risk taking and instrumental value of the group [22]. It is presumed that when cohesion is high, the group is motivated to perform well and is more able to coordinate activities for successful performance [23]. The role of cohesion within a group has been extensively investigated in psychotherapy and it has been shown that higher group cohesion predicted better treatment outcome [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Group cohesion has been described as a bonding force consisting of four factors, namely attraction to the group as a whole and to individual members of the group, risk taking and instrumental value of the group [22]. It is presumed that when cohesion is high, the group is motivated to perform well and is more able to coordinate activities for successful performance [23]. The role of cohesion within a group has been extensively investigated in psychotherapy and it has been shown that higher group cohesion predicted better treatment outcome [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prior studies have been proven the positive and significant relationship between team cohesion and the performances of players (Alemu & Babu, 2012;Beal, Cohen, Burke, & McLendon, 2003;Brawley, Carron, & Widmeyer, 1993;Bray & Whaley, 2001;Carron & Chelladurai, 1981a;Carron, Bray, & Eye, 2002;Carron, Colman, Wheeler, & Stevens, 2002;Chang, Duck, & Bordia, 2006;Jacob & Carron, 1998;Manning, 2007;Murray, 2006;Mullen & Copper, 1994;Mohd Zainal & Rosli, 2012;Williams & Widmeyer, 1991;Eys, Ohlert, Evans, Wolf, Martin, Bussel, & Steins, 2015). Murray (2006) study analysis revealed significant relationship between team cohesion and performance.…”
mentioning
confidence: 94%
“…First, "leadership effectiveness behavior" was the team members' evaluation of actions or behaviors of leaders relevant to team performance (Beal, Cohen, & Burke 2003;Campbell et al 1993). Following Campbell et al (1993), we included measures of actions (such as problem solving) that were the result of unobservable cognitive behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…One potential explanation for this finding derived from implicit theories of leadership (e.g., Lord 1985) is that the effect of vocal attractiveness on leadership effectiveness should pertain only to leadership perceptions and not to leadership outcomes because traits that predict perceptions are not necessarily those that predict "the performance of a leader's work group or organization" (Lord, De Vader, & Alliger, 1986, p. 408). Therefore, like other implicit leadership traits, vocal attractiveness should be a good predictor of leadership effectiveness behaviors and not of leadership effectiveness outcomes, which does not take into account the many potential impediments to performance that are beyond the effects of perceived leadership behaviors (Beal et al 2003;Campbell 1990;Campbell et al 1993). It is important to note that also in Study 2, our control for cognitive ability, a paper and pencil measure of intelligence, was not significantly related to leadership effectiveness behaviors, but was significantly and positively related to leadership effectiveness outcomes.…”
Section: Theoretical Implicationsmentioning
confidence: 99%